Investigation of residual stresses in planar dissimilar magnetic pulse welds by neutron diffraction. (August 2021) - Avettand-Fènoël, M.-N.; Sapanathan, T.; Pirling, T.; Racineux, G.; Simar, A.; Drezet, J.-M.
Abstract: Residual stresses are investigated for the first time in a dissimilar AA1050–DP450 steel magnetic pulse weld using neutron diffraction. Close to the joint interface, tensile residual stresses are observed in the Al sheet and compressive residual stresses are identified in the steel sheet. At the interface, longitudinal tensile stresses are dominant on the aluminum side and transverse and normal stresses show similar behavior. On the steel side, normal stresses remain small, and longitudinal and transverse residual stresses have a similar trend. It was identified that close to this tensile region in aluminum, residual stresses in steel become more compressive. These residual stress distributions essentially result from (i) the respective yield strengths of Al and steel and (ii) the high strains and high strain rates borne by both alloys due to the impact of the Al flyer sheet on the steel sheet during the process. The asymmetrical shape of the rectangular joint line entailed a lower magnitude of residual stresses along the short side of the weld.